SARS-CoV, MERS-CoV and SARS-CoV-2: A Diagnostic Challenge - Ezhilan, Madeshwari (Measurement (Lond), 2021)
The highly pathogenic MERS-CoV, SARS-CoV and SARS-CoV-2 cause acute respiratory syndrome and are often fatal. These new viruses pose major problems to global health in general and primarily to infection control and public health services. Accurate and selective assessment of MERS-CoV, SARS-CoV and SARS-CoV-2 would assist in the effective diagnosis of infected individual, offer clinical guidance and aid in assessing clinical outcomes. In this mini-review, we review the literature on various aspects, including the history and diversity of SARS-CoV-2, SARS-CoV and MERS-CoV, their detection methods in effective clinical diagnosis, clinical assessment of COVID-19, safety guidelines recommended by World Health Organization and legal regulations. This review article also deals with existing challenges and difficulties in the clinical diagnosis of SARS-CoV-2. Developing alternative diagnostic platforms by spotting the shortcomings of the existing point-of-care diagnostic devices would be useful in preventing future outbreaks.